Gastric Metastasis of Primary Lung Cancer: Case Report and Systematic Review With Pooled Analysis - Tang, Dong; Lv, Jianjian; Liu, Zhijing; Zhan, Shuhui; Gao, Yuqiang (Frontiers in Oncology, 2022)
Background Gastric metastasis from lung cancer (GMLC) is a rare occurrence. The clinicopathological characteristics, outcomes and prognostic factors remain largely elusive. Methods We conducted a systematic review on case reports and case series of GMLC by scanning Medline, EMBASE, and ISI Web of Knowledge. Data involving the clinicopathological features, treatment, and outcomes were extracted and analyzed. Survival analysis was performed using Kaplan-Meier method. The Cox proportional hazards regression model was used to identify potential prognostic factors associated with survival. Furthermore, a case of metastatic gastric adenocarcinoma of pulmonary origin with epidermal growth factor receptor (EGFR) L858R+T790M mutation was also described and included. Results Seventy-eight records involving 114 cases (including ours) were finally included. The median age at present was 65 years with a male predominance of 79.8%. Lung adenocarcinoma (42.1%), located in the right upper lobe (30.3%), was the most frequent primary tumors. Bleeding (36.7%) and abdominal pain (35.8%) were the two most common symptoms. Endoscopically, gastric lesions were typically presented as elevated lesions with or without volcano-like ulceration, or ulcerative lesions, mostly involving the gastric corpus. The median overall survival time and survival time after diagnosis of metastatic cancer were 11 months (95% confidence interval [CI] 7 - 14) and 4.5 months (95% CI 3 - 9), respectively. The survival analyses revealed that surgical interventions (including lung surgery, and/or abdominal surgery), and systemic therapy (including chemotherapy, radiotherapy, and/or targeted therapy) seemed to be positive prognostic factors for both overall survival and survival after diagnosis of metastatic cancer. Conclusions Clinicians should be alert to the occurrence of gastric metastasis in lung cancer patients. Comprehensive evaluation and appropriate treatment for specific patients may improve the survival rate of GMLC patients.